PH-sensitive polymeric micelles for the Co-delivery of proapoptotic peptide and anticancer drug for synergistic cancer therapy. Issue 21 (24th February 2017) - Mozhi, Anbu; Ahmad, Israr; Okeke, Chukwunweike Ikechukwu; Li, Chan; Liang, Xing-Jie
Abstract : pH-sensitive polymeric micelles for targeted co-delivery of mitochondria-damaged proapoptotic peptide and DTX for synergistic cancer therapy. Abstract : Mitochondria plays a vital role in a wide range of biological processes in human health and diseases. They are considered to be important organelles responsible for cellular apoptosis or programmed cell death. Therefore, the targeting of chemotherapy towards mitochondria would be highly desirable. Herein, we developed a pH-sensitive polymer that is designed for the subcellular co-delivery of anticancer drugs and therapeutic peptides to tumor cells. The amphiphilic copolymer poly(β-amino esters)-poly(ethylene glycol) was synthesized and conjugated with the dual-targeting proapoptotic peptide CGKRKD (KLAKLAK)2 . The conjugate can self-assemble into a core–shell micellar structure at the physiological pH of 7.4. The anticancer drug docetaxel (DTX) was encapsulated inside the core of the micelles. The CGKRK peptide is specifically targeted to angiogenic blood vessels in tumors and tumor cells, whereby the micelles are efficiently internalized into tumor cells via an energy-dependent, lipid draft/caveolae-mediated endocytosis pathway. Once inside the acidic endosomal compartment, the stimuli-responsive micellar carriers disassemble and release both pharmacological agents. CGKRK efficiently transportsD (KLAKLAK)2 towards mitochondria to trigger mitochondria-dependent apoptosis. DTX affects microtubulin for arresting the cancer cell cycle. Thus, the combination of DTX and the therapeutic peptide displayed a synergistic antitumor effect in an MCF-7 cell line.